Guidance on memorizing the Qur'an at SDI Insan Mandiri Cihaur Simpenan Sukabumi - U Abdullah Mu’min; Acip; Landiansyah; Vini Anggraeni; Weni Yulianti; Ani Nuraeni; Ati Sulastri; Miranti Nurkhofifah (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
This research aims to help and provide guidance in memorizing the Al-Qur'an to SDI Insan Mandiri children in reading and memorizing the Al-Qur'an. The method of guiding memorizing the Qur'an for elementary school children is an approach that requires special attention, patience, and the right approach to help elementary school children in the process of memorizing the Qur'an. In teaching and learning activities, SDI Insan Mandiri children read and memorize the Al-Qur'an, which is guided directly by KKM STAI Palabuhanratu students in class V as a form of community service, especially in the field of education at SDI Insan Mandiri, Cihaur Village. With guidance on memorizing the Qur'an at SDI Insan Mandiri, it is hoped that SDI Insan Mandiri children will get used to reading the Qur'an every day and have memorized the Qur'an for provisions in this world and the afterlife.